A Discussion on the Reasons for Excessive Average Preoperative Hospitalization Days. (July 2014) - Liu, Jiali; Chen, Zixing
Abstract Objective. To discuss the factors influencing the standard test indexes of the average length of stay of a patient before elective surgery. Methods. The reasons were identified by analyzing cases of extra-long duration of stay before elective surgery in the first half of 2013 of a 3A hospital. Results. The reasons were physician enrollment, more than two elective operations in one instance of hospitalization, elective surgery, and failure in the treatment of the main disease; before intervention, the preoperative average length of stay was 3.53 days, and was reduced to 2.7 days after intervention. Conclusion. A formulated library of names of elective surgery, the removal of choices irrelevant to checking, and the creation of computerized audit programs, automatic screening of index time calculation, and so on, helped to check and continuously improve the levels of medical management.